The equilibrium phase diagram of the pentaerythritol-pentaglycerine-2-amino-2methyl-1, 3, propanediol (PE-PG-AMPL) system. (September 2019) - Mishra, Amrita; Shi, Renhai; Chandra, Dhanesh; Gantan, Ivan
Abstract: Polyalcohols and amines have been considered as potential thermal energy storage materials, owing to their energetic solid-solid phase transitions. In this paper, we present equilibrium phase diagram of Pentaerythritol (PE)–Pentaglycerine (PG)– 2-amino-2methyl-1, 3, propanediol (AMPL) ternary system that has been thermodynamically assessed using the CALPHAD method. A special class of, so called, " Plastic Crystals " have tetrahederally configured molecules with O–H⋯O or N–H⋯O layered or chained bonds in the low temperature phase, and store latent heat of transformation during solid-solid phase change in orientationally disordered crystals at higher temperatures. For example, in polyalcohols, there are O–H⋯O bond rotations around the C–C bonds that are responsible for storing large amounts of solid state phase change energy. Several binary equilibrium phase diagrams of polyalcohols, amines and combination thereof have been calculated and experimentally validated. We only know of three ternary phase diagram of these plastic crystals reported, to the best of knowledge. In the thermodynamic calculations of the PE-PG-AMPL system, we used the binary phase diagram experimental data for the optimization and calculation of excess energies. The binary systems have been optimized using regular and sub-regular solution models. The binaries as well as the ternary system have been calculated from room temperature to the liquid phase. The solution phases are modeled as substitutional solutions, in which the excess Gibbs energies are expressed by the Redlich–Kister–Muggianu polynomial. There is a very good agreement between previously reported experimental data and the calculated phase diagrams.